x^3 - x^3 = 0 Remember , whilst 'x' is an unknown value, that unkonwn is a fixed value. As a numerical example 3^(3) - 3^(3) = 27 - 27 = 0 The '3' is 'x' in this case
No because 3 cubed is 27 which is a rational number
27X^3-8 = 0 27X^3 = 8 X^3 = 8/27 X = cubic root of 8/cubic root of 27 = 2/3
To calculate 2 squared (2^2), you multiply 2 by itself, resulting in 4. To calculate 3 cubed (3^3), you multiply 3 by itself three times, resulting in 27. Finally, to find the product of 2 squared and 3 cubed, you multiply 4 by 27, resulting in 108.
3 cubed means 3x3x3. To start, 3x3=9. Then, 9x3=27. That's all there is to it.
4x2 + 6x - 3 (with no remainder)
x^3 - x^3 = 0 Remember , whilst 'x' is an unknown value, that unkonwn is a fixed value. As a numerical example 3^(3) - 3^(3) = 27 - 27 = 0 The '3' is 'x' in this case
993
(4x - 3)(16x^2 + 12x + 9)
0.75
27 cubed is equal to 19683.
3x3x3+3/3
3 cubed is equal to 27.
9 / (-1/3) = -27
33
3 cubed is 27. 3 in expanded form is 3x3x3.
3 cubed = 3x3x3 27